The role of Pharmacy shops in the management of acute uncomplicated childhood Diarrhoea in Ghana. - Amoa, A.H.; Ofori- Adjei, D. (Ghana Medical Journal, 1988)
Advice and prescription for acute uncomplicated diarrhoea in children under five years given at pharmacy shops and the availability of Oral Rehydration Salts (DRS) was studied in the city of Accra, Ghana. A Public Health Nurse acting as the mother of a fictitious child with acute diarrhoea sought advice {rom 37 randomly selected pharmacy shops and purchased all recommended treatment. 33 out of the 37 shops sold drug items to the mother. Only two shops (5.4%) sold her ORS. The rest dispensed kaolin/pectin/antibiotic combinations. None asked the mother to seek medical advice. Eight shops gave instructions as to how to prepare home-made oral rehydration solutions only on request. There is the need {or continuing public education all the value of DRS in preventing dehydration in Ghana. The strategy for ORS distribution also requires revision
Journal Article
Keywords: Diarrhea in under-fives Oral rehydration salts; pharmacy shops; Oral Rehydration Salts (ORS); Ghana